Analisis Ekonomi Traktor Roda Empat Harfia Tipe HTR 445 di Brigade Alsintan Dinas Pertanian dan Perikanan Kota Tomohon - Songga, Julmiati; Molenaar, Robert; Wullur, Hildy (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2025)
The application of technology in the agricultural sector is the use of agricultural tools and machinery. Equipment and machinery enable farmers to increase efficiency, productivity, and product quality. Furthermore, agricultural tools and machinery will enhance social status and the environment. One effort to increase efficiency in farming is the use of mechanical power, such as tractors for land processing. The main reason for shifting from manual to mechanization is the crucial role of agricultural tools and machinery in supporting the continuous increase in agricultural production. In an effort to increase the efficiency and effectiveness of agricultural machinery use, economic analysis of the tractors used is necessary. The research results showed that the total cost was IDR 121,827 per hour. The break-even point was achieved at land processing of approximately hectares per year. The feasibility analysis of the Harfia HTR 445 tractor based on the Net Present Value (NPV) calculation was IDR 328,757,162. The Benefit-Cost Ratio was 1,18. The Internal Rate of Return (IRR) was 22%. Based on the results obtained, the Harfia HTR 445 four-wheel tractor is economically feasible. Keywords: Tractor, Efficiency, Economic Analysis